Wearable Sensors: Flexible Hybrid Sensors for Health Monitoring: Materials and Mechanisms to Render Wearability (Adv. Mater. 15/2020). Issue 15 (14th April 2020) - Gao, Yuji; Yu, Longteng; Yeo, Joo Chuan; Lim, Chwee Teck
Abstract : Wearable electronics brings forth revolutionary changes toward digital health monitoring. Skin conformable sensors enable real‐time health monitoring and non‐invasive disease detection and diagnosis. With the advancement of flexible hybrid materials, as discussed by Joo Chuan Yeo, Chwee Teck Lim, and co‐workers in article number 1902133, the future of personalized healthcare and imperceptible monitoring is highly anticipated. Image by Melanie Lee, Mechanobiology Institute.